OPPORTUNITIES OF BIOMECHANICAL ANALYSIS OF SPORTS MOVEMENTS BASED ON ARTIFICIAL INTELLIGENCE - Q. Yu. Suvonov (American Journals, 2025)
This article analyzes the theoretical foundations, practical opportunities, and prospects of using artificial intelligence (AI) technologies in sports biomechanics. The effectiveness of modern approaches developed based on machine learning, computer vision, and neural networks for biomechanical assessment of sports movements is highlighted. Furthermore, the study examines the use of AI for improving sports techniques, preventing sports injuries, and optimizing training processes. The results of the research demonstrate that the use of digital technologies in sports biomechanics has significant scientific and practical value.
Keywords: Sports biomechanics, artificial intelligence, biomechanical analysis, machine learning, sports movement, technique, injury prevention.